DESIGN OF A WEBSITE-BASED HOSPITAL DATA SEARCH DATABASE SYSTEM FOR COVID-19 AND NON-COVID-19 PATIENTS - Rachmaniar, Ani; Diana, Desy; Riastuti, Marti (Journal of Information System, Informatics and Computing; Vol 7 No 2 (2023): JISICOM (December 2023)DO - 10.52362/jisicom.v7i2.1275, 2023)
The Covid-19 virus pandemic has made people anxious because of the availability of hospitals that accept Covid patients. Many hospitals restrict or even reject people because of the large number of cases that cause death. The difficulty of finding data on hospitals that accept Covid patients for treatment has made many people worried. This research was conducted based on information from public complaints in searching for information on existing data in hospitals that receive Covid-19 patients. The development of this information system was carried out using the classic method or SDLC Spiral which is commonly known as the waterfall method. The waterfall method uses a linear and sequential software development approach, where each development phase, such as planning, analysis, design, implementation, testing and maintenance, is carried out sequentially and cannot be started until the previous phase is complete. The aim of this research is to build a hospital database design for Covid patients, to make it easier for Covid patients to find data on hospitals that accept Covid patients. The research results in the form of an information system in the form of a website application can be used by users, especially Covid patients. The research results can be measured by testing the function of the web-based application information system with the conclusion that the website can run well and access to each menu runs quite well. The web browser used for testing is Google Chrome but you can use the browser according to the device used. The success of the application based on the results of the survey that was carried out to get a point meter of 0-10 was 5 people choosing a value of 8 and the rest choosing a value above 5..